2016
DOI: 10.1117/1.nph.3.1.010401
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the statistical properties of noise and its implication on general linear models in functional near-infrared spectroscopy

Abstract: Abstract. Functional near-infrared spectroscopy (fNIRS) is a noninvasive neuroimaging technique that uses low levels of light to measure changes in cerebral blood oxygenation levels. In the majority of NIRS functional brain studies, analysis of this data is based on a statistical comparison of hemodynamic levels between a baseline and task or between multiple task conditions by means of a linear regression model: the so-called general linear model. Although these methods are similar to their implementation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
254
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(282 citation statements)
references
References 34 publications
3
254
0
1
Order By: Relevance
“…13 In addition, we have recently detailed several methods for improved time-series analysis and generalizations of the linear model to deal with fNIRS specific noise structures. 11,35,36 In this work, we have presented an analysis pipeline combining these recent advancements that allows all Table 3 Spatial correlation. The correlation of the activation patterns between the estimated localizer responses.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, we have recently detailed several methods for improved time-series analysis and generalizations of the linear model to deal with fNIRS specific noise structures. 11,35,36 In this work, we have presented an analysis pipeline combining these recent advancements that allows all Table 3 Spatial correlation. The correlation of the activation patterns between the estimated localizer responses.…”
Section: Discussionmentioning
confidence: 99%
“…In baseline correction, we defined a period starting from the onset of the task condition to the end of each task condition as one analysis block. Then, we applied linear regression by least mean squares to determine the linear trend of its baseline [62,63]. Finally, data were averaged in all the analysis blocks [64].…”
Section: Pre-processingmentioning
confidence: 99%
“…Deviations from this expected rate indicate uncontrolled or overcontrolled type I errors in the model as detailed in Ref. 33. In these results, at this threshold, the actual FDR of the OLS model is under-reported with a value between FDR ¼ ½0.1; 0.2.…”
Section: Simulation Resultsmentioning
confidence: 84%
“…Thus, fNIRS data containing motion artifacts often result in a nonuniform noise distribution with outliers and a heavy-tailed noise distribution (reviewed in Ref. 33). Barker et al 27 showed that prewhitening to remove serially correlated errors and robust regression to deal with heteroscedasticity of the motion artifacts was effective in improving GLM estimation in fNIRS data.…”
Section: Introductionmentioning
confidence: 99%